SWOT ANALYSIS FOR MATERNAL REFERENCE IN HEALTH DEPARTMENT OF SIDOARJO DISTRICT - Kartika Sri Redjeki (JURNAL PENELITIAN KESEHATAN, 2016)
Background: National Health System briefed the availability of good health services which carriedout with due regard to innovations and breakthroughs in proper implementation, continuous,integrated and plenary through the strengthened of the referral system. The disadvantage ofhealth services is the implementation of referrals less rapid and not precise.Objective: Arranged recommendations related to maternity referral system  for HealthDepartment of Sidoarjo DistrictMethods: This was quantitative analytical research. Design of the study was cross-sectional studyusing the method of observation. Samples were employees in the Health Family Section on Healthdepartment of Sidoarjo District. The sample size in this study were 10 people. The samplestechnique was purposive sampling method.Results: First step was observations at Health Family Section of Health Departmen SidoarjoDistrict and analyzed using SWOT, the result was located in quadrant SO (Strength-Opportunity).Based on assessments, the strategy of "Develop program EMAS throughout the territory of districtsin Sidoarjo for the improvement of the referral system" to obtain a total value of 15, while thestrategy of "Building a commitment to health services including the entire Hospitals private repairreferral system" scored 13, so it was determined that the strategy "Develop program EMASthroughout the territory of Sidoarjo regency to repair referral system "become a top prioritystrategy executed in the development of the referral system in Sidoarjo District.Conclusions: Interventions and efforts to manage the referral system Mothers delivery in order toreduce maternal mortality in the Health Service Sidoarjo were done well in the community, at thelevel of basic services and the service level of reference, there have been a decrease in the numberof maternal deaths in the first half of this year compared to half last year, and the program EMASin one region (vanguargd network) has helped to integrate the basic level of service up to areference level.Keywords: Referral system, SWOT, Program EMAS,  Maternity.